Torturing the Artist: Celebrity and Trope in Media Representations of the Abstract Expressionists. - Cavise, Phoebe. (Tufts Archival Research Center, 2018)
This thesis explores the means and effects of the media’s use of the Tortured Artist trope in building Celebrity. In particular, Jackson Pollock and Mark Rothko are used as case studies in understanding this ongoing process of “celebritization.” The topic is examined through analyzing significant representations of the artists in the media published during their lifetimes and today - the latter being Ed Harris’ feature film Pollock (2000) and John Logan’s play Red (2009), both award-winners in their respective fields. Their contents aim to demonstrate how postwar American values determined the art-historical worth of two of the country’s most important modern artists, while their formal qualities demonstrate the same for today’s society. In addition, a theatrical production of Red, directed by the thesis author, was completed on March 8, 9, and 10, 2018, and the thesis concludes with a first-person account of its pedagogy and staging.